Correlation between male and female genital tuberculosis: a prospective analytical study - Chaudhary, Aarushi; Kaur, Prabhjot; Kansal, Richa; Dhillon, Vikas; Bansal, Isha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Genital tuberculosis is an unusual extrapulmonary manifestation of tuberculosis, often seen in middle-aged men with renal or pulmonary disease. The most common male genital sites of tuberculous infection are the epididymis and prostate. It is also an important cause of female infertility in the world, especially in developing countries. Majority of infertility cases are due to involvement of the fallopian tubes. Hardly any study has been done to establish correlation between male and female genital TB. We have evaluated the same in severe oligospermic/ azoospermic males and established a definite correlation. Objective was to establish a definite correlation between female and male genital tuberculosis in patients with male factor infertility. Methods: 100 severe oligozoospermic/azoospermic males presenting with infertility between April 2011 and January 2016 were enrolled and worked up for genital tuberculosis. Their female partners were worked up for female genital TB and correlation established. Results: Out of 100 patients with severe oligospermia or azoospermia who tested positive for TB quantiferon gold test. 18% female partners tested positive for TB quantiferon gold test. Conclusions: Tubercular work up of both partners is desired in couples with male factor infertility especially in long standing infertility to achieve optimum pregnancy outcome with ART.